2021
DOI: 10.1109/tap.2020.3030992
|View full text |Cite
|
Sign up to set email alerts
|

Omnidirectional Dual-Polarized Low-Profile Textile Rectenna With Over 50% Efficiency for Sub-μW/cm2 Wearable Power Harvesting

Abstract: Despite the recent advances in textile antennas, in complete systems such as a rectenna, the efficiency of fully-textile solutions has been over 46% lower than hybrid textile/rigid implementations. This paper presents a fully-textile rectenna for ultra-low power sub-µW/cm 2 applications. A dual-polarized omnidirectional low-profile textile antenna is presented. The rectenna is based on a compact inductively-matched rectifier. The textile-based rectifier occupies 0.22 cm 2 and achieves a state-ofart Power Conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 46 publications
2
92
0
Order By: Relevance
“…4 shows the measured charging PCE Average at 433 and 915 MHz, where it can be observed that the rectifier achieves at least 10% average charging PCE. In [14], it was previously shown that for a single-series rectifier the average charging PCE is approximately 66% lower than the peak optimal load PCE. Nevertheless, the peak average PCE of the proposed rectifier is only 58% lower than its optimal load PCE, showing its suitabtility for directly charging a supercapacitor.…”
Section: B Supercapacitor-loaded Rectifier Characterizationmentioning
confidence: 98%
See 2 more Smart Citations
“…4 shows the measured charging PCE Average at 433 and 915 MHz, where it can be observed that the rectifier achieves at least 10% average charging PCE. In [14], it was previously shown that for a single-series rectifier the average charging PCE is approximately 66% lower than the peak optimal load PCE. Nevertheless, the peak average PCE of the proposed rectifier is only 58% lower than its optimal load PCE, showing its suitabtility for directly charging a supercapacitor.…”
Section: B Supercapacitor-loaded Rectifier Characterizationmentioning
confidence: 98%
“…1-b. It was previously shown that inductive matching, combined with a miniaturized layout to maintain a high {Z in }, can achieve a high PCE even on a lossy substrate or conductors [14]. The chosen diode is the Infinion BAT15-04R reverse-pair Schottky diode, the diode was chosen based on its forward voltage (under 300 mV) and its relatively high breakdown voltage of 4 V, enabling high-PCE at a wider input power range than low-breakdown diodes such as the SMS7630.…”
Section: Rectifier Design and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Textile rectennas are mostly based on off-body antennas [5]- [9], due to their improved isolation. More recently, widebeam omnidirectional "wire-type" antennas such as monopoles were investigated for wearable applications [10]- [12]. While textile-based rectifiers have been used in [5] and [8], their Power Conversion Efficiency (PCE) has been lower than a rigid low-loss rectifier coupled to a textile patch antenna [7].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from works already included in Table 1, [26,27] present two almost pure textile rectennas working at 0.8 GHz, with peak PCE of up to 63.9% at sub-µW/cm 2 power density levels, providing extremely promising results especially for Wireless Power Transfer (WPT) applications.…”
Section: Introductionmentioning
confidence: 99%